Thermal load in a medium-sized European city using the example of Aachen, Germany - Buttstädt, Mareike; Schneider, Christoph (ERDKUNDE, 2014)
In this paper we focus on air temperature and its distribution within a medium-sized European city (Aachen) to identify those areas where high levels of thermal load are likely to be observed. The temperatures for the whole city area are examined by means of a GIS-based model. This approach based on mobile measurements demonstrates the distribution of air temperature differences in relation to a reference station and allows for a detailed analysis of the influencing factors of urban structure and land use. Despite the fact that air temperature distribution in Aachen is largely determined by terrain, the influences of land use and urban structures are apparent in the model results. The evaluation of afternoon and evening air temperature data for the summer half-year (April–September) show that the importance of factors contributing to thermal load varies in the course of the day. During daytime the highest air temperature arises in industrial areas with a high degree of surface sealing. However, during the evening inner-city residential quarters with a dense building structure show the highest thermal load. Forest and green spaces also determine the specific air temperature patterns but their impact varies in the course of the day and with the size of neighborhood used for correlation statistics. The spatial structure of the modeled temperature distribution is in accordance with the spatial structure of the surface radiant temperatures from a thermal image over wide areas of Aachen. Deviations are obvious for buildings whose roof materials cause surface temperatures that differ significantly from air temperatures modeled for the 2 m level. Furthermore, the comparison makes obvious the limits of the model: the effects of cold air drainage flows and wind directions cannot be assessed. However, this is not considerably detrimental to the results.